2008
DOI: 10.1017/s1368980007000341
|View full text |Cite
|
Sign up to set email alerts
|

Associations between salivary bacteria and reported sugar intake and their relationship with body mass index in women and their adolescent children

Abstract: Objective: To study associations between reported sugar intake and salivary bacteria (mutans streptococci, MS and lactobacilli, LB), and sugar intake in relation to body mass index (BMI), in women and adolescents. Design: Cross-sectional study. Habitual dietary intake was reported in a questionnaire and whole saliva samples were collected and cultivated. Setting: Stockholm, Sweden. Subjects: Four hundred and fourteen mothers and their 16-year-old children (57% girls). Results: Reported total sugar intake was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…Many papers later indicated that the level of salivary lactobacilli (but also of mutans streptococci) is sensitive to dietary saccharide intake (van Houte et al 1994), however, this association has been proven to be generally weak due to the lack of high standard experimental studies (Vågstrand et al 2008). Salivary bacteria could not be used as an indicator of sugar intake on an individual level as their counts are distorted by many confounding factors, such as salivary flow, oral hygiene etc., but could be used on a population level (Vågstrand and Birkhed 2007).…”
Section: Lactobacillimentioning
confidence: 99%
“…Many papers later indicated that the level of salivary lactobacilli (but also of mutans streptococci) is sensitive to dietary saccharide intake (van Houte et al 1994), however, this association has been proven to be generally weak due to the lack of high standard experimental studies (Vågstrand et al 2008). Salivary bacteria could not be used as an indicator of sugar intake on an individual level as their counts are distorted by many confounding factors, such as salivary flow, oral hygiene etc., but could be used on a population level (Vågstrand and Birkhed 2007).…”
Section: Lactobacillimentioning
confidence: 99%
“…1,2 Studies using mixed cultures grown in chemostats have shown that the increase in cariogenic organisms in biofilm does not occur due to sugar availability per si, but in response to the low pH associated to sugar catabolism. It is the ability of acid-tolerant microorganisms to survive in the low-pH environments that promotes their selection of, and thriving in, such acidic environments.…”
Section: Introductionmentioning
confidence: 99%
“…High counts of MS in saliva can be used as a biomarker for intake of fermentable carbohydrates (14) , and positive associations between MS and BMI have been identified in adults (15)(16)(17) but not in children (18) or adolescents (17) . Given the obesity epidemic, the link between overweight and risk of dental caries is of interest.…”
mentioning
confidence: 99%